Autonomy and ethnic conflict in South and South-East Asia - Ganguly, Rajat (Asian security studies., 2012)
This book uses empirical evidence from various case studies to examine the relationship between territorial and regional autonomy, the nation-state and ethnic conflict resolution in South and South-East Asia. The concept of territorial or regional autonomy holds centre stage in the literature on ethnic conflict settlement because it is supposed to be able to reconcile two paradoxical objectives: the preservation of the territorial integrity and sovereignty of the state, and the satisfaction of ethnic minorities' right to national self-determination. Critics argue, however, that autono.